Pengaruh Kecerdasan emosional dan komunikasi serta budaya organisasi terhadap kinerja karyawan TVRI Samarinda - Rosy Hardi Fazrin; Djoko Setyadi; Robiansyah Robianyah (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study to determine the effect of emotional intelligence, communication and culture of secret societies on employee performance TVRI Samarinda. Basic theory used my human resources management by means of multiple linear regression analysis with a sample of 60 employees.The conclusion of this study:T value variable emotional intelligence t tables and significance 0.05 indicates a significant effect of emotional intelligence teradap employee performance TVRI Samarinda. Thus the hypothesis that emotional intelligence is a significant and positive effect on employee performance TVRI Samarinda, thus the research hypothesis is acceptedT value variable communication t tables and significance 0.05 indicates significant influence communication teradap employee performance TVRI Samarinda. Thus, the hypothesis put forward Communications positive and significant effect on employee performance TVRI Samarinda accepted, thus the research hypothesis is acceptedT value of organizational culture variables t tables and significance 0.05 indicates significant influence communication teradap employee performance TVRI Samarinda. Thus, the hypothesis put forward organizational culture positive and significant effect on employee performance TVRI Samarinda accepted, thus the research hypothesis is accepted.Keywords: Emotional Intelligence, Communication, Organizational Culture - Performance